Targeting gut microbiota for diabetic nephropathy treatment: probiotics, dietary interventions, and fecal microbiota transplantation - Wang, Xiaoran; Liu, Xinyin; Gong, Fanghong; Jiang, Yan; Zhang, Canwei; Zhou, Wei; Zhang, Wen (Frontiers in Endocrinology, 2025)
Diabetic nephropathy (DN) stands as a prominent microvascular complication of diabetes mellitus and presents a significant global health challenge. Despite advancements in glycemic control and renin-angiotensin system inhibition, current treatments merely delay disease progression without targeting fundamental pathological processes. This review explores gut microbiota modulation as a promising treatment strategy for DN through probiotic supplementation, dietary interventions, and fecal microbiota transplantation(FMT) protocols. The gut microbiota, integral to the “gut-kidney axis,” is critically implicated in DN pathogenesis. DN is associated with gut dysbiosis—characterized by reduced microbial diversity, depletion of beneficial short-chain fatty acid (SCFA)-producing bacteria, and proliferation of opportunistic pathogens. This dysbiosis impairs gut barrier integrity, fostering systemic inflammation and the accumulation of uremic toxins like indoxyl sulfate. Furthermore, translocated bacterial lipopolysaccharides activate Toll-like receptors and the NLRP3 inflammasome, exacerbating kidney damage and fibrosis. Interventions targeting the microbiota, including dietary strategies (e.g., enhancing fermentable fibers, low-protein diets) and FMT, show promise in preclinical and early clinical studies, though FMT requires stringent safety and donor screening protocols. Significant challenges persist, such as managing inter-individual microbiota variability for personalized therapies, fully elucidating molecular mechanisms like SCFA-GPR43 signaling, and leveraging multiomics for biomarker discovery. Advancing microbiota-focused interventions for DN towards microbiome-centered precision medicine necessitates addressing standardization, deepening mechanistic understanding, and validating combination therapies, heralding a potential shift from traditional nephroprotective approaches.